The Influence of Leadership Style and Work Discipline on Employee Job Satisfaction at the Department of Personnel and Human Resource Development Bandung Regency - Rahayu, Anik; Dayona, Gurawan; Sudaryo, Yoyo (Jurnal sosial dan sains, 2025)
In the era of globalization has changed the way of life of traditional society into a modern society. The lifestyle of modern society generally prefers something that is fast, practical, easy and comfortable. To face this competition, every company must be able to develop and manage its resources such as: material capital and machines and even its human resources. In a company, employees are an important factor for the company, because employees have the ability, energy and creativity needed by the company to achieve its goals. This study aims to analyze "The Influence of Leadership Style and Work Discipline on Employee Job Satisfaction at the Department of Civil Service and Human Resource Development (BKPSDM) of Bandung Regency". This study uses a quantitative method with a descriptive and verification approach. Data were collected through a questionnaire with 60 respondents and the analysis technique used was descriptive analysis, with the Validity and Reliability Test method and Multiple Regression Analysis. Meanwhile, this test uses SPSS 20. Therefore, 32.1% of employees like the Leadership Style of the current leader, 42.1% of employees still have good discipline so that leadership style and discipline greatly influence employee satisfaction which will improve a comfortable, orderly work atmosphere and comply with applicable regulations.